Evergreen Production System for Southern Highbush Blueberries in Florida - Doug Phillips; Jeffrey G Williamson; Patricio R Munoz (EDIS)
In central and south-central Florida, many southern highbush blueberries (SHB) are grown in an evergreen system, in which the plants do not go dormant, and are managed to retain their leaves from the previous year through harvest the following spring to support early flowering and fruit set. The evergreen system has also been used under tunnels in north-central Florida. This new 3-page publication of the UF/IFAS Horticultural Sciences Department, written by Douglas A. Phillips, Jeffrey G. Williamson, and Patricio R. Munoz, provides an overview of the evergreen production system for SHB in Florida.